Single- and Multi-Frequency Detection of Surface Displacements via Scanning Probe Microscopy - Romanyuk, Konstantin
Piezoresponse force microscopy (PFM) provides a novel opportunity to detect picometer-level displacements induced by an electric field applied through a conducting tip of an atomic force microscope (AFM). Recently, it was discovered that superb vertical sensitivity provided by PFM is high enough to monitor electric-field-induced ionic displacements in solids, the technique being referred to as electrochemical strain microscopy (ESM). ESM has been implemented only in multi-frequency detection modes such as dual AC resonance tracking (DART) and band excitation, where the response is recorded within a finite frequency range, typically around the first contact resonance. In this paper, we analyze and compare signal-to-noise ratios of the conventional single-frequency method with multi-frequency regimes of measuring surface displacements. Single-frequency detection ESM is demonstrated using a commercial AFM.